Potential of extracellular space for tissue regeneration in dentistry - Birjandi, Anahid A.; Sharpe, Paul (Frontiers in Physiology, 2022)
With the proven relationship between oral and general health and the growing aging population, it is pivotal to provide accessible therapeutic approaches to regenerate oral tissues and restore clinical function. However, despite sharing many core concepts with medicine, dentistry has fallen behind the progress in precision and regenerative treatments. Stem cell therapies are a promising avenue for tissue regeneration, however, ethical, safety and cost issues may limit their clinical use. With the significance of paracrine signalling in stem cell and tissue regeneration, extracellular space comprising of the cell secretome, and the extracellular matrix can serve as a potent source for tissue regeneration. Extracellular vesicles are naturally occurring vesicles with biologically active cargo that can be harvested from the extracellular space. These vesicles have shown great potential as disease biomarkers and can be used in regenerative medicine. As a cell free therapy, secretome and extracellular vesicle can be stored and transferred easily and pose less ethical and safety risks in clinical application. As there are currently many reviews on the secretome and the biogenesis, characterization and function of extracellular vesicles, here we look at the therapeutic potential of extracellular space to drive oral tissue regeneration and the current state of the field in comparison to regenerative medicine.